DESIGN AND OPTIMIZATION OF MODULAR PRODUCTION SYSTEM PICK & PLACE STATION - Siva, Farrell; Purna Irawan, Agustinus; Halim, Agus; Widya Utama, Didi (Program Studi Teknik Mesin Universitas Tarumanagara, 2023)
In the industrial era 4.0 where the development of sophisticated technology, the development of technology has been increasingly rapid. The industry itself began to use this sophisticated technology with the aim of seeking maximum profit with minimum capital, so for that reason the industry began to switch to